2022
DOI: 10.3390/ijerph19159262
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Randomized Pilot Study on the Benefits of Baby Swimming on Motor Development

Abstract: According to the concept of “embodied cognition”, motor development should not be considered distant from cognitive and language processes. Motor development is essential in the first 1000 days of life, as the child explores and learns new information from the environment. Among motor activities, baby swimming allows infants to make movements that they are not able to perform on solid ground. Since movements become slower in water, the sensory perception of these movements is amplified. However, the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…One pilot study [ 39 ] pointed to an increase in developmental percentile (measured using AIMS) after baby swimming program intervention. Similar results were found in cross-sectional studies showing significant improvements in gross [ 40 , 41 , 43 ], fine, and total motor development [ 41 ] in infants participating in swimming programs when compared with the control groups and that four-year-old children who previously participated in baby swimming programs had better scores in prehension (ball skills) and in static balance (one-leg balance) than children that did not participate in baby swimming programs [ 38 ]. In cognitive performance, no significant pre- or post-test differences were found in either the intervention or control group, only a marginal tendency towards intervention-related gains in inhibition speed and response selection (or shifting) accuracy [ 41 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…One pilot study [ 39 ] pointed to an increase in developmental percentile (measured using AIMS) after baby swimming program intervention. Similar results were found in cross-sectional studies showing significant improvements in gross [ 40 , 41 , 43 ], fine, and total motor development [ 41 ] in infants participating in swimming programs when compared with the control groups and that four-year-old children who previously participated in baby swimming programs had better scores in prehension (ball skills) and in static balance (one-leg balance) than children that did not participate in baby swimming programs [ 38 ]. In cognitive performance, no significant pre- or post-test differences were found in either the intervention or control group, only a marginal tendency towards intervention-related gains in inhibition speed and response selection (or shifting) accuracy [ 41 ].…”
Section: Resultssupporting
confidence: 89%
“…The positive effect on child neurodevelopment reported by Garcia and colleagues in their systematic review [ 17 ] was confirmed for infants younger than 36 months in the present review. Although three studies had already been included in Garcia et al’s review [ 38 , 39 , 48 ], more recent studies confirmed the positive effects of aquatic activities exposure on infants’ development [ 41 , 42 , 43 , 49 ]. Baby swimming programs were associated with improvements in gross, fine, and total motor development [ 39 , 40 , 41 , 43 ] (even when the children are older [ 38 ]); improvement in motion perception [ 42 ]; and a tendency for an improvement in early executive function skills [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Motor development refers to the ability of children to move and interact with the environment and is very important in early childhood [ 1 ]. Proper motor development provides an opportunity for children to explore and participate in the world around them [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Swimming offers various benefits for children's development, including physical, cognitive, and psychosocial aspects. Research has shown that swimming can improve lung function in children with asthma, enhance motor development in infants, and reduce cardiometabolic risk in children and adolescents with overweight and obesity (Leo et al, 2022;Machado et al, 2022).…”
Section: Introductionmentioning
confidence: 99%